Dinamika Sosial Kebijakan Kesehatan: Penyakit Kelamin dalam Modernisasi Militer Praja Mangkunegaran (1860–1910) - Lucia Arter Lintang Gritantin; Umar Hi. Rajab; Rusli M. Said (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2026)
This study investigates the spread of venereal diseases, particularly syphilis and gonorrhea, in the Mangkunegaran Principality during the second half of the nineteenth century by examining the interplay between military modernization, colonial governance, and public health. It addresses the question of how the Mangkunegaran authorities responded to the growing prevalence of these diseases amid increasing interaction with the Dutch colonial administration. Employing the historical method through heuristic inquiry, source criticism, interpretation, and historiography, the study analyzes archival records, colonial regulations, and contemporary historical sources, with particular attention to the Reglement op de Publieke Vrouwen (1852). The findings demonstrate that the spread of venereal diseases was closely associated with military mobility, prostitution, and expanding colonial social networks, prompting the adoption of more systematic health surveillance and regulatory measures. These developments marked a gradual transition from indigenous healing practices toward institutionalized public health policies shaped by colonial medical discourse. The study concludes that the management of venereal diseases in Mangkunegaran reflected not only medical concerns but also broader transformations in state administration, social control, and colonial intervention in nineteenth-century Java.